ANALISIS KONTRIBUSI SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN LANDAK - B01109020, Avilla Erni (Jurnal Pembangunan dan Pemerataan, 2015)
The agricultural sector is one of the first sectors since our beloved country is experiencing a difficult time in its history (the financial crisis) were able to survive and continue to contribute to the field in the form of business and jobs for the State. The government was aware of this, by the development of the agricultural sector sebeb continuously performed not only by the government but also by the public agency with the various constraints faced by the government and the community work done in order to agriculture increased in every year so as to prop up the economy and society increase the value of GDP in Porcupine District. To determine the increase in the agricultural sector in this study Porcupine District using time series data that his next analyzed using descriptive analysis Contributions and analysis. Based on the analysis of the general contribution of the agricultural sector in the Porcupine District continues to decline from the period 2007 to 2012 but very dominant influence economic growth in the Porcupine District. Keywords: contribution to economic growth